CONSEPTUAL PAPER EMPLOYEE PERFORMANCE - Wahyu Anggoro, Febrian Setyo; Widodo, Arry; Silvianita , Anita; Rubiyanti, Nurafni (FEB Universitas Sam Ratulangi Manado, 2024)
This research aims to determine the relationship between work discipline, work environment, and work motivation on employee performance using student data from the Department of Industry and Trade, Tabanan Regency, Bali, Export Import Control and Distribution Section. This research applies quantitative descriptive methods. To determine the sample size, a saturated sample approach is used, that is, taking the entire population. The approach adopted is Structural Equation Model (SEM), analyzed using Smart-PLS. The research results show that work motivation is the most important antecedent of employee performance, followed by work discipline and work environment. Work Motivation acts as a mediating variable between work discipline and work environment and employee performance. This research has several implications for companies in improving employee performance. Companies need to improve strong work discipline, create a good work environment for employees.